Estudio de prefactibilidad para la instalación de una planta procesadora de néctar de arazá (Eugenia stipitata Mc Vaugh) - Del Castillo Luis, Cinthya Lorena (2020)
This preliminary study has for aim evaluate the viability of the implementation of a producing factory of néctar of arazá. Through this study will figure out in all of diverse chapters if the project is feasible from de point of view of the market study, technological, economic and financial.